Widespread rash as initial presentation of acute hepatitis E in a woman with well-controlled HIV. (June 2021) - Pringle, Rachel; van Halsema, Clare
Sporadic, acute hepatitis E is increasingly common in the United Kingdom, associated with travel or locally acquired. A 45-year-old woman with well-controlled HIV presented with a widespread, polymorphic rash and transaminitis. Acute genotype 3 hepatitis E infection was confirmed and resolved without intervention. A review of the literature reveals a number of atypical presentations of acute autochthonous hepatitis E. Clinicians should consider testing for hepatitis E in the presence of nonspecific symptoms and deranged liver function tests.